Logic and its applications : 8th Indian Conference, ICLA 2019, Delhi, India, March 1-5, 2019, Proceedings /: 8th Indian Conference, ICLA 2019, Delhi, India, March 1-5, 2019, Proceedings. (2019) - Unknown
No abstract available